A Combined Smoking Cessation Intervention within a Lung Cancer Screening Trial: A Pilot Observational Study. Issue 3 (May 2015) - Pozzi, Paolo; Munarini, Elena; Bravi, Francesca; Rossi, Marta; La Vecchia, Carlo; Boffi, Roberto; Pastorino, Ugo
Aims and Background: The time of lung cancer screening may provide the ideal setting to discuss and initiate a smoking cessation plan that includes pharmacologic aids. No studies to date have fully investigated the potential effectiveness of such combined approach. Methods: We prospectively evaluated the biochemically verified 1-year continuous abstinence rate from smoking of 187 persistent smokers enrolled within the Multicentric Italian Lung Detection Trial (MILD), who received a pharmacologic aid to quit smoking with varenicline along with behavioral counseling. The propensity of study subjects to succeed in smoking cessation was also monitored. Results: At 12 months, the continuous abstinence rate from smoking was achieved in 37 out of 187 patients (19.8%), with a propensity to succeed in smoking cessation for the assisted attempt equal to 1.43, as compared to an unassisted MILD patient. At the end of the third month of therapy, 48.7% of subjects showed a continuous abstinence rate, while only 33.7% of patients were abstinent from smoking at 6 months. At baseline, the subgroup of MILD participants who were originally allocated to lung tomography showed higher smoking intensity than those allocated to no screening. Conclusions: A combined smoking cessation intervention can be implemented with satisfactory results within a lung cancer screening program; this preliminary observation needs to be replicated in a prospective investigation. Clinicians should consider that lung cancer screening may be falsely reassuring for persistent smokers; therefore it should always be coupled with a smoking cessation program.